Augmented Reality Utilization for Mathematical Thinking Skills in Indonesian Junior High Schools - Juwita Rini; Eko Pradipta Kurnaedi; Nurul Husnah Mustika Sari; Rhischa Assabet Shilla (Hipotenusa: Journal of Mathematical Society, 2025)
Augmented Reality (AR) is one of the technologies used in Indonesian junior high school mathematics learning. This study aims to conduct a systematic literature review on the use of AR and its influence on mathematical thinking skills at the junior high school level from 2020 to 2024. Mathematical thinking skills in this study are focused on students' problem-solving skills, reasoning skills, creative thinking skills, and critical thinking skills The Systematic Literature Review method is used by reviewing, analyzing, and synthesizing findings from 11 previous empirical studies on augmented reality articles at the junior high school level related to mathematical abilities (problem solving, reasoning, creative thinking, or critical thinking) conducted in Indonesia, sourced from the Google Scholar database (indexed Sinta 1 to Sinta 3) and Scopus (articles and proceedings) published in 2020-2024, in English or Indonesian, and full-text articles are available. This study found that researchers have used various methods to investigate AR in junior high school mathematics education, with quasi-experimental designs, often involving control groups, being the most common. Geometry emerged as the most frequently studied topic. AR-based instruction has been shown to improve junior high school students' mathematical skills in Indonesia, demonstrating a significant impact on academic achievement and critical thinking compared to traditional methods, while also enhancing reasoning and problem-solving abilities. The potential challenges of integrating augmented reality into junior high school mathematics instruction include the need for sufficient technological devices, teachers' technological competencies, and effective learning time management.